1991
DOI: 10.1007/bf00024593
|View full text |Cite
|
Sign up to set email alerts
|

The role of endogenous auxin in root initiation

Abstract: This paper describes the process of the formation of adventitious roots . There appears to be good agreement that this consists of four stages, dedifferentiation coupled with the formation of a meristematic locus, cell division to form a radially symmetrical cluster of cells, further divisions coupled with organisation into a bilaterally symmetrical meristem and finally growth of cells in the basal part of the meristem which causes its protursion through the epidermis. Evidence for the involvement of auxins in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0
3

Year Published

1991
1991
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(33 citation statements)
references
References 55 publications
5
25
0
3
Order By: Relevance
“…These differences probably occurred because we were comparing results of experiments in which different species had been used. After the decrease of IAA level in the late initiation phase (Jarvis 1986;Blakesley et al 1991) the renewed increase of IAA is known in the phase of growth and development of root primordia (Tartoura et al 2004) which is supported by our results. There were no differences in auxin dynamics between the mature and juvenile stockplant material which suggests that the differences in endogenous IAA between both types of material at the time of severance are the most important factor for the subsequent root formation.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These differences probably occurred because we were comparing results of experiments in which different species had been used. After the decrease of IAA level in the late initiation phase (Jarvis 1986;Blakesley et al 1991) the renewed increase of IAA is known in the phase of growth and development of root primordia (Tartoura et al 2004) which is supported by our results. There were no differences in auxin dynamics between the mature and juvenile stockplant material which suggests that the differences in endogenous IAA between both types of material at the time of severance are the most important factor for the subsequent root formation.…”
Section: Discussionsupporting
confidence: 87%
“…Although, the differences were not significant the use of juvenile cutting material with higher amounts of IAA in tendency demonstrated how important the endogenous auxin level could be when examining better rooting results of this material. Blakesley et al (1991) have already summarised that endogenous auxin level in cuttings should be very important for the later root formation, but this question was rarely included in the experiments. Later on, various authors (Spethmann 1997;Hartmann et al 1997) have already underlined endogenous auxin level in the cutting bases as the central point in the successful rooting process in plants, but they also mentioned the exogenous auxin which can serve as a counterpart in the rooting process.…”
Section: Discussionmentioning
confidence: 98%
“…The results indicated a typical increase-decrease variation in free IAA concentration during the first 5 d that correspond to the induction of rooting; this variation is similar to that observed in other rooting materials (Maldiney et al 1986;Blakesley et al 1991;Gaspar et al 1992Gaspar et al , 1994Blakesley 1994). Moncousin et al (1988, and Noiton et al (1992) have shown that this transitory IAA peak corresponded to the end of the rooting inductive phase.…”
Section: Discussionsupporting
confidence: 78%
“…It is considered that the optimum concentration of IAA for the initiation of rooting is markedly supraoptimal for root extension. Thus IAA can be stimulatory at an early stage but inhibitory at a later one [14,6] . Maldiney et al, [17] have suggested a similar interpretation of the stimulatory and inhibitory effects of ABA .…”
Section: Introductionmentioning
confidence: 99%